Genome-Wide Comparative Analyses Reveal the Dynamic Evolution of Nucleotide-Binding Leucine-Rich Repeat Gene Family among Solanaceae Plants - Seo, Eunyoung; Kim, Seungill; Yeom, Seon-In; Choi, Doil (Frontiers in Plant Science, 2016)
Plants have evolved an elaborate innate immune system against invading pathogens. Within this system, intracellular nucleotide-binding leucine-rich repeat (NLR) immune receptors are known play critical roles in effector-triggered immunity (ETI) plant defense. We performed genome-wide identification and classification of NLR-coding sequences from the genomes of pepper, tomato, and potato using fixed criteria. We then compared genomic duplication and evolution features. We identified intact 267, 443, and 755 NLR-encoding genes in tomato, potato, and pepper genomes, respectively. Phylogenetic analyses and classification of Solanaceae NLRs revealed that the majority of NLR super family members fell into 14 subgroups, including a TIR-NLR (TNL) subgroup and 13 non-TNL subgroups. Specific subgroups have expanded in each genome, with the expansion in pepper showing subgroup-specific physical clusters. Comparative analysis of duplications showed distinct duplication patterns within pepper and among Solanaceae plants suggesting subgroup- or species-specific gene duplication events after speciation, resulting in divergent evolution. Taken together, genome-wide analyses of NLR family members provide insights into their evolutionary history in Solanaceae. These findings also provide important foundational knowledge for understanding NLR evolution and will empower broader characterization of disease resistance genes to be used for crop breeding.